2022
DOI: 10.1111/nyas.14892
|View full text |Cite
|
Sign up to set email alerts
|

Putting music to trial: Consensus on key methodological challenges investigating music‐based rehabilitation

Abstract: Major advances in music neuroscience have fueled a growing interest in music-based neurological rehabilitation among researchers and clinicians. Musical activities are excellently suited to be adapted for clinical practice because of their multisensory nature, their demands on cognitive, language, and motor functions, and music's ability to induce emotions and regulate mood. However, the overall quality of music-based rehabilitation research remains low to moderate for most populations and outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 124 publications
(279 reference statements)
1
14
0
Order By: Relevance
“…For general recommendations on developing RTC music intervention research, refer to the recent consensus publication by (Grau-Sánchez et al, 2022).…”
Section: Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…For general recommendations on developing RTC music intervention research, refer to the recent consensus publication by (Grau-Sánchez et al, 2022).…”
Section: Limitationsmentioning
confidence: 99%
“…Poetry slam training consequently would have a higher likelihood of showing improvements in the speech outcome than music training. A recent article by Grau-Sánchez et al (2022) provides general recommendations for choosing active control groups for music-based training.…”
Section: Music Training and Skill Transfermentioning
confidence: 99%
“…Moreover, because training of auditory–motor synchronization was found to improve executive functions (e.g., inhibition control) in typical development, 102–104 rhythmic training may be generally beneficial for a range of disorders. In most of the cases, the assessment of the benefits of auditory–motor synchronization in neurodevelopmental disorders awaits randomized control trials, including a comparable active control condition 18 . Rhythmic serious games can be instrumental for this purpose by providing a viable alternative to implement training protocols by taking advantage of their motivating and inclusive properties.…”
Section: Discussionmentioning
confidence: 99%
“…The advantage of these technologies that allow for remote interventions is even more evident in a time of pandemics when in‐person interventions are impossible, or in the case of isolation or reduced mobility (for reviews, see Refs. 9 and 18).…”
Section: Introductionmentioning
confidence: 98%
“…Studying the effect of music-based interventions in medical contexts is complex and requests strong methodology. Discussion with researchers in this field suggested that the main methodological research challenges relate to treatment, outcomes, research designs, and implementation ( 37 ). According to a systemic review, music sessions should last between 20 and 60 min and consist principally of harmonic variations ( 38 ).…”
Section: Introductionmentioning
confidence: 99%